2021
DOI: 10.1007/s11606-021-06842-1
|View full text |Cite
|
Sign up to set email alerts
|

Development of the Verbal Autopsy Instrument for COVID-19 (VAIC)

Abstract: Background Improving accuracy of identification of COVID-19-related deaths is essential to public health surveillance and research. The verbal autopsy, an established strategy involving an interview with a decedent’s caregiver or witness using a semi-structured questionnaire, may improve accurate counting of COVID-19-related deaths. Objective To develop and pilot-test the Verbal Autopsy Instrument for COVID-19 (VAIC) and a death adjudication protocol using it. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, the procedure for mapping answers to diagnostic codes had to be modified for a new diagnosis, SARS-CoV-2. The specific modification we employed has not yet been validated – although other modifications to the WHO VA instrument to address COVID have been 24,25 . Nevertheless, assessments of VA modifications to capture SARS-CoV-2 show there is error and diagnosis should be complemented with minimally invasive techniques such as ultrasound when the decedent’s cadaver is available 26 .…”
Section: Discussionmentioning
confidence: 99%
“…However, the procedure for mapping answers to diagnostic codes had to be modified for a new diagnosis, SARS-CoV-2. The specific modification we employed has not yet been validated – although other modifications to the WHO VA instrument to address COVID have been 24,25 . Nevertheless, assessments of VA modifications to capture SARS-CoV-2 show there is error and diagnosis should be complemented with minimally invasive techniques such as ultrasound when the decedent’s cadaver is available 26 .…”
Section: Discussionmentioning
confidence: 99%
“…Most studies, however, have reported favorable outcomes for the VA, albeit based on poor quality and low robustness comparisons of data on cause of death, which affects the questionnaire validation 27 . Modifications have therefore been made to improve the accuracy of the VA, such as the creation of a diagnostic stratification system to categorize cases as unlikely, possible, probable, and definite 28 , and a version of the VA that uses a community-based mechanism to identify suspected COVID-19-related deaths at the population level 29 .…”
Section: Discussionmentioning
confidence: 99%
“…Second, to supplement official COVID-19 surveillance, point-in-time questionnaires, patient interviews or other verbal reporting mechanisms may help improve surveillance of COVID-19 transmission in contexts where testing or surveillance is limited, particularly in countries where the national government is coping with significant resource and capacity constraints, such as in South Sudan [56,57]. Assessing relatively rare cases of mortality which may carry stigma through survey instruments in a fragile or conflictaffected context, however carries limitations as well, often leading to underreporting, as found in relation to measurement of maternal mortality in Afghanistan [58].…”
Section: Recommendationsmentioning
confidence: 99%